Avaliação da satisfação de reabilitações com implantes zigomáticos - Brackmann, Mariana Schaffer (2017)
AbstractIntroduction Rehabilitation of patients with atrophic maxilla is challenging. Atrophic maxilla patients present compromised quality of life, impaired function, deficient nutrition, social and emotional difficulties. The rehabilitation of atrophic maxilla by zygomatic fixtures has been previously proposed.Objective This retrospective study evaluated the degree of satisfaction of patients rehabilitated by immediately loaded conventional and zygomatic fixtures supporting full-arch fixed dental prosthesis. A satisfaction questionnaire was used for patient assessment.Material and method Nineteen patients treated at the Latin American Institute for Dental Research and Education (ILAPEO) between December 2005 and June 2010 were evaluated. Patients were rehabilitated with 41 zygomatic implants and 73 conventional implants under immediate load.Result All assessed patients were completely satisfied with the provided rehabilitation.Conclusion It can be concluded that rehabilitation with zygomatic fixtures is capable of restoring function, phonetics, and esthetic for patients with atrophic maxilla. The patients were satisfied with the treatment outcomes and showed increased self-esteem after the rehabilitation.